SPEAKING SKILL ASSESSMENT ON ENGLISH TEACHERS AND THEIR INNOVATION IN TEACHING AT THREE SENIOR HIGH SCHOOLS WITH DIFFERENT BACKGROUND IN TELUK KUANTAN - YOFFIE KHARISMA DEWI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
The competency in speaking English should be owned and mastered by all English teachers. They should become the appropriate model for their students in and outside the classroom. Students generally expect their English teacher to be good mostly at speaking. They tend to imitate and learn from their teachers, particularly in the level of speaking. Speaking English, as one of the productive skills, cannot be assessed directly and objectively by unqualified and inexperienced assessor. Therefore, there are scoring guide of speaking assessment and scale criteria used in assessing. Data were obtained from nine English teachers from three different high schools in Teluk Kuantan; MAN Teluk Kuantan (a state Islamic high school), SMAN Pintar Kuansing (a superior state boarding school funded by government), and SMAN 1 Teluk Kuantan (a state senior high school). The assessments of English teachers’ speaking skill were undertaken from the records of daily conversation, their interaction in the classroom, interview, and the questionnaire sheet given to the students. The result shows that those teachers generally had good speaking skill but there were some aspects in speaking assessment not fulfilled. Those aspects are pronunciation, grammar accuracy, vocabulary, and fluency. The highest score went to Mr. S from MAN Teluk Kuantan, with his teaching innovations were student-centred-learning, project-based-learning, and social network-based-learning. Ms. D (SMAN 1 Teluk Kuantan) and Ms. Ar (SMAN Pintar Kuansing) were in the second and third ranking. Here shown that the superior school could not guarantee its teachers had speaking skill better than other schools’ teachers.